Parental Variables as Correlates of Career Preference Among Secondary School Students in Public Schools in Bayelsa State - Felicia Mark Welson Bodisere (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study investigated parental variables as correlates of career preference among secondary school students in Bayelsa State. The study was guided by three research questions and three hypotheses, tested at the 0.05 level of significance, using a correlational research design. A sample of 400 Senior Secondary II (SS II) students was selected through stratified random sampling. Data were collected using the Vocational Interest Inventory (VII) and a self-constructed Parental Variable Questionnaire (PVQ), both validated by experts in Measurement and Evaluation. Reliability was established using the Cronbach Alpha method, yielding coefficients of 0.844 for the PVQ and 0.802 for the VII. Pearson Product Moment Correlation was used for data analysis. The findings revealed significant relationships between parental occupation, parental income, and parental level of education, and students’ career preferences. Based on these findings, it was recommended that parents should provide guidance and support to their children in making career choices without imposing decisions, thereby allowing them to pursue careers that align with their interests and abilities. Government and relevant stakeholders should provide scholarships and financial assistance to students from low-income families to enable them to achieve their desired career goals.